Exploring the Practice of Academic Freedom and Active Learning in Ethiopia's Higher Education: A Case Study Markos - Tezera Taye; Ahmed Alduais (Athens Institute for Education and Research, 2022)
Given the immense role of the student-centred approach in enhancing students learning, this study explores the role of academic freedom in implementing a student-centred approach. To achieve this objective, the study relies on a qualitative case study research design. In this regard, semi-structured interviews and observation were employed as data gathering tools. The data passed through a series of data analysis processes ranging from data reduction to data verification. The study was conducted at a public university in Ethiopia and recruited ten instructors and twelve students from four randomly selected colleges/institutes belonging to the participating university. The initial analysis resulted in two major themes, each having two subthemes. That is academic freedom at the institutional level for instructors and students and academic freedom at the classroom for instructors and students. Given this, the findings show that the academic freedom of students at the classroom level affects the adoption of student-centred approaches. Students seem to be restrained from freely sharing their concerns, being afraid of the backlash from their instructors and colleagues. Moreover, the instructors in Abay University seem excluded in deciding to implement a student-centred approach in every classroom other than receiving pedagogical training to implement it as a non-negotiable change. These findings call for higher education reforms at national and institutional levels to cultivate an organisational environment that facilitates student-centred approaches.